Luminescent biodegradable polycaprolactone materials prepared by blending with bio-based hyperbranched polymers - Si Qi Huang; Wen Hong Ruan; Ze Pu Wang; Ming Qiu Zhang (eXPRESS Polymer Letters, 2022)
It is the pursuit to give biodegradable polycaprolactone (PCL) luminescence properties while maintaining its biocompatibility in a feasible way. For this purpose, bio-based luminescent furan-terminated hyperbranched polymers (HBPFs) have been synthesized, and the degrees of branching (DB) of HBPFs are varying from 0.47 to 0.55 as the changing feeding ratio of monomers. All HBPFs exhibit low glass transition temperature (Tg), great fluidity, and bright yellow fluorescence in solution under ultraviolet (UV) light. The ultraviolet/visible (UV/Vis) and fluorescence spectra show that the HBPFs have characteristics of cluster-induced emission (CIE) from the non-conventional chromophores with the concentrations increased. Furthermore, PCL-based materials blending with the HBPFs are also prepared. It is found that the PCL-based blends emit white fluorescence, and the fluorescence intensity is influenced by the contents and DB of HBPFs. The morphologies of HBPFs/PCL show that the HBPFs with low contents and high DB is well-distributed in PCL, which is conducive to electron transmission and groups-clustering, further enhancing fluorescence emission. The rheological analysis reveals that HBPFs could decrease the viscosity of blends, indicating that HBPFs can play a role as flow modifiers in melt processing. Crystallization behaviors show that the crystallization degree (Xc) of PCL is increased owing to the effects of heterogeneous nucleation of HBPFs (i.e. Xc for neat PCL is 60.3% while 5 wt%HBPF-3/PCL is 71.9%). As a result, the modulus of PCL blends is improved. This kind of biocompatible blends with good comprehensive properties and fluorescence characteristics are expected to be applied in the preparation of biomedical materials for in-situ non-invasive detection.